Imagining the COVID-19 pandemic through the minds of 9–11 years old: findings from an art exhibition in India. (March 2021) - R, Amrutha; Sadh, K.; Murthy, P.
Abstract: Objectives: To understand children's perspectives of COVID-19 and lockdown through art. Study design: Observational; Qualitative study. Methods: The drawings and descriptive notes along with the drawings were presented in an art exhibition and were thematically analyzed. Results: Forty-three documents were created, out of which 134 quotations, 24 codes, 21 themes, and six groups were synthesized. The themes were mainly related to positive experiences, negative experiences, unity, safety, hope, uncertainty, gratitude, faith, and future expectations. Conclusion: This study contributes to a better understanding of children's perspectives of the pandemic situation. Highlights: The world is going through difficult and unimaginable times in this pandemic era. An art exhibition was organized for children to use their time creatively and to better understand COVID-19. The children's artworks portray the situation as perceived by the young eyes and minds.